Constraints encountered by the dairy farmers in adapting to coping strategies during drought in Bundelkhand region of Uttar Pradesh - Sankhala, Gopal ---; SINGH, MANESH; KANT, KAMALA; PRASAD, KAMTA (Indian Journal of Dairy Science, 2016)
Increase in total milk production is mainly attributed to the huge bovine population, but productivity per animal is still very low. Basically milk production and productivity depends upon managemental as well as environmental factors. Managemental factors include mainly breeding, feeding, healthcare and other management practices whereas, environmental factors include drought, flood, temperature, wind speed, etc. Among these environmental factors, drought is a very serious obstruction which reduces the productivity of livestock in many ways. In this context, the present study was conducted in Bundelkhand region of Uttar Pradesh to delineate the constraints experienced by the dairy farmers in adapting to coping strategies during drought and to enlist the suggestions of the dairy farmers. Data were collected through personal interview and focus group discussion from the total 160 respondents using both qualitative and quantitative techniques. The data were analysed using weighted mean, rank, frequency and percentage. The findings of present study show that the major constraints were lack of knowledge of feeding practices during drought, non-availability of credit facilities for adapting to drought, low purchasing power to purchase the veterinary medicines, lack of availability of veterinary service and lack of support from government, lack of resources, non reaching of government facilities to every farmers, lack of awareness about government schemes regarding drought, low milk yield, shortage of green fodder and poor conception.